IMPROVING GROWTH AND PRODUCTIVITY OF EUPHORBIA ANTISYPHILITICA: A BIOFUEL PLANT FOR SEMI-ARID REGIONS: Pharmaceutical Science-Botany - JOHARI, SHOBHA; ASHWANI KUMAR (International Journal of Life Science and Pharma Research, 2013)
Photosynthetic organisms use solar energy to generate reducing equivalents and incorporate atmospheric CO2 into organic molecules. Worldwide production of biodiesel increased by 60% in 2005, and ethanol by 19% over the previous year’s production, as per World watch Institute, USA. Countries like Thailand are aiming for a 10% renewable mix in the next five years; India 20% by 2020. Sweden has stated that it aims to become 100% energy independent by 2020; most of this independence will come through its own nuclear power, but renewable fuels will likely make up the balance. However there is considerable concern for competition between food and fuel if food crops are used for biodiesel production. Euphorbia antisyphilitica grows well in semi arid regions of the world and could be ideal for biofuel production. During present investigations edaphic conditions promoting biofuel production were studied and improvement in biofuel production is reported.